Internacionalização das empresas: perspectivas, motivação e barreiras - Costa, Marcos Antonio Cordeiro. (2017)
Defined by the involvement of companies with foreign operations in the form of products, services or investments, internationalization has become a factor of crucial attention for organizations as a response to an integrated and competitive global market. Thus, this paper aims to approach the theme internationalization emphasizing the main motivations, barriers and strategies associated with this process. This is a qualitative-descriptive study conducted through a bibliographic research and presents the main theories of internationalization, such as Market Power, Eclectic Paradigm and Uppsala Model. This study shows how different perspectives (economic, behavioral and cultural) can influence the reasons and the way companies lead their international expansion, besides presenting different strategies of internationalization, such as exports, licensing and the establishment of foreign facilities. It was observed that companies decide to internationalize in order to exploit their advantages, increase their profits and reduce costs, but the lack of knowledge of the markets and the process of internationalization are obstacles that can jeopardize their international expansion. In addition, it is presented the context of the Brazilian experience with internationalization, which has been strongly influenced by government supportive mechanisms and measures that led to the development of an export culture. It is concluded that, even without intention, organizations are becoming participants in global business and internationalization emerges as an alternative that allows companies to become more competitive in today's global economic context.